"Ang Pilipinas bilang lupain ng kabalintunaan:" Si Isabelo De Los Reyes bilang tagapag-ambag sa pahayagang La Solidaridad (1889-1895) - Liwanag, Leslie Anne L. (Animo Repository, 2019)
© 2019, Plaridel. The project aims to inductively understand and to make an impartial assessment on the articles of Isabelo de los Reyes in the Philippine periodical La Solidaridad (1889-1895). The paper is significant in the sense that this will help towards the understanding on the motives and contribution of the articles in the imagination of the Philippine society. It will also enrich the current studies about the polymath who spent most of his time giving service to the Philippine nation. To achieve such goals, this paper contains five substantive sections: 1) an intellectual biography of de los Reyes as a writer and journalist; 2) contents of de los Reyes' articles in La Solidaridad; 3) some themes and discourses of de los Reyes' articles in La Solidaridad; and the 4) critical conclusion on his thoughts and contribution in the said periodical.